Analysis of Factors Associated With Rhytidectomy Malpractice Litigation Cases - Kandinov, Aron (JAMA Facial Plast Surg, 2017)
IMPORTANCE: This study investigates the financial burden of medical malpractice litigation associated with rhytidectomies, as well as factors that contribute to litigation and poor defendant outcomes, which can help guide physician practices. OBJECTIVE: To comprehensively evaluate rhytidectomy malpractice litigation. DATA SOURCES AND STUDY SELECTION: Jury verdict and settlement reports related to rhytidectomy malpractice litigations were obtained using the Westlaw Next database. Use of medical malpractice in conjunction with several terms for rhytidectomy, to account for the various procedure names associated with the procedure, yielded 155 court cases. Duplicate and nonrelevant cases were removed, and 89 cases were included in the analysis and reviewed for outcomes, defendant specialty, payments, and other allegations raised in proceedings. Data were collected from November 21, 2015, to December 25, 2015. Data analysis took place from December 25, 2015, to January 20, 2016. RESULTS: A total of 89 cases met our inclusion criteria. Most plaintiffs were female (81 of 88 with known sex [92%]), and patient age ranged from 40 to 76 years (median age, 56 years). Fifty-three (60%) were resolved in the defendant’s favor, while the remaining 36 cases (40%) were resolved with either a settlement or a plaintiff verdict payment. The mean payment was $1.4 million. A greater proportion of cases involving plastic surgeon defendants were resolved with payment compared with cases involving defendants with ear, nose, and throat specialty (15 [36%] vs 4 [24%]). The most common allegations raised in litigation were intraoperative negligence (61 [69%]), poor cosmesis or disfigurement (57 [64%]), inadequate informed consent (30 [34%]), additional procedures required (14 [16%]), postoperative negligence (12 [14%]), and facial nerve injury (10 [11%]). Six cases (7%) involved alleged negligence surrounding a “lifestyle-lift” procedure, which tightens or oversews the superficial muscular aponeurosis system layer. CONCLUSIONS AND RELEVANCE: In this study, although most cases of rhytidectomy malpractice litigation were resolved in the defendant’s favor, cases resulting in payments created substantial financial burden for the defendants. Common factors cited by plaintiffs for pursuing litigation included dissatisfaction with cosmetic outcomes and perceived deficits in informed consent. These factors reinforce the importance of a comprehensive, preoperative informed consent process in which the specific potential risks and outcomes are presented by the surgeon to the patient to limit or avoid postsurgical allegations. Intraoperative negligence and facial nerve injury were significantly more likely to result in poor defendant outcomes. LEVEL OF EVIDENCE: NA.